2014
DOI: 10.1007/s10995-014-1477-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Birth Outcomes by Mother’s Country of Birth Among Non-Hispanic Black Women in the United States

Abstract: Rates of prematurity (PTB) and small-for-gestational age (SGA) were compared between US-born and foreign-born non-Hispanic black women. Comparisons were also made between Sub-Saharan African-born and Caribbean-born black women and by maternal country of birth within the two regions. Comparisons were adjusted for sociodemographic, health behavioral and medical risk factors available on the birth record. Birth record data (2008) from all states (n = 27) where mother’s country of birth was recorded were used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 40 publications
3
62
0
1
Order By: Relevance
“…The estimated difference in preterm birth risk between infants where there is no divergent ancestry and those with completely divergent ancestry is 7.5%. This number approximates the entire difference in risk between people of European and African American ancestry, 29 but the actual difference in divergent ancestry that we observed between African American and European ancestry infants was much smaller.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The estimated difference in preterm birth risk between infants where there is no divergent ancestry and those with completely divergent ancestry is 7.5%. This number approximates the entire difference in risk between people of European and African American ancestry, 29 but the actual difference in divergent ancestry that we observed between African American and European ancestry infants was much smaller.…”
Section: Discussionmentioning
confidence: 57%
“…2628 In addition, studies of immigrant and nonimmigrant mothers of African ancestry have observed that immigrant mothers, who may have less admixture than women whose families have been in the US for many generations, have lower rates of preterm birth. 29,30 One caveat is that environmental exposures and stressors could also be responsible for the difference in preterm birth risk between immigrant and nonimmigrant populations. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Research conducted outside the US has tended to focus more on differences by maternal country of birth as opposed to race or ethnicity, with consistently higher preterm birth risks reported among women born in sub-Saharan Africa and the Caribbean than among women born in France, Canada or the Netherlands. 13,15,35 In the US, foreign-born black women have considerably lower preterm birth risk than native-born black women, 17,36 but it is not known whether this pattern holds in other countries. We detected no advantage in preterm birth risk among foreign-born versus native-born black women in Canada, with our results instead suggesting higher preterm and very preterm birth risk among foreign-born black women than among native-born black women in Canada (preterm birth rate 9.2% v. 8.3%; very preterm birth 2.1% v. 1.4%).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Although the magnitude of these differences is smaller than the disparity in preterm births between black and white women in the US, 16 foreign-born black women in the US have been found to be at lower risk of preterm birth than US-born black women. 17,18 In both Canada and the US, socioeconomic conditions at both individual and neighbourhood levels are important predictors of preterm birth. [19][20][21] Although the income gap between black and white people is markedly smaller in Canada than in the US, 22 black populations in both countries have lower education levels, higher unemployment rates and a greater likelihood of living in low-quality neighbourhoods compared with white populations.…”
mentioning
confidence: 99%